Collective attention in navigating homing pigeons: group size effect and individual differences - Kano, F; Sasaki, T; Biro, D (Elsevier, 2021)
One prominent feature of collective attention is the so-called ‘group size effect’. Often documented in studies of vigilance by animals foraging gregariously, this effect describes how individual group members are able to reduce their attention to environmental cues (e.g. predators) as group size increases, since the group can pool information from multiple individuals. Despite extensive literature in one context (foraging–vigilance), it remains unclear whether this effect can be observed in other contexts where animals face different informational demands (e.g. navigation). Using a custom-made sensor combining head-mounted inertial measurement unit and back-mounted GPS, we examined head movement, a proxy for visual scanning behaviour, in homing pigeons, Columba livia, flying alone, in pairs and in flocks (ca. 10 individuals). Individual birds' head movements decreased sharply when they switched from solo to paired flights and again when they switched from paired to flock flights. Homing efficiency (or route straightness) did not decrease in parallel with decreasing head movement but continued to increase over repeated flights. We also found systematic individual differences during flock homing flights, where birds positioned more frontally and more centrally in the flock made larger head movements. Moreover, leaders were positioned more frontally and tended to show larger head movements than followers. Decreased head movement by peripheral birds suggested increased attention to the rest of the flock rather than increased individual vigilance (contra ‘the edge effect’). Overall, our results suggest that individual birds reduced their visual scanning during navigation because of the need to attend closely to fellow flock members to maintain flock cohesion. While reduced per capita visual scanning may reduce the amount of environmental information available to individual birds, it is likely to be compensated by the flock's collective attention.